Perkembangan Makroekonomi Negara Kanada Dengan Analisa Vector Error Correction Model (VECM) - I Wayan Sunarya (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
This study aims to analyze the relationship between Gross Domestic Product (GDP), Inflation (INF), Import (IMP) and Unemployment (UEM) that occurred in Canada by using Vector Error Correction Model (VECM) analysis. The data source comes from https://www.imf.org; data taken from 1980 to 2020. The analytical tool used is the Vector Error Correction Model (VECM) which aims to analyze the relationship or causality between variables both in the short and long term, where the results obtained are the relationship between variables more referring to short term causality. And to find out the impact between variables, this study uses an Impulse Response Function (IRF) analysis where the results that have a positive impact during the Covid-19 pandemic are import shocks to GDP in Canada while the results that have a negative impact are import shocks on unemployment and also Canada's unemployment rate against GDP during the COVID-19 pandemic.